Factors Affecting the Employability of Selected BSHM Graduates of Bestlink College of the Philippines A.Y. 2021-2022: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employability is a set of skills, qualities, and accomplishments that improve graduates'chances of landing jobs and succeeding in their chosen fields, which benefits the person, theworkforce, the community, and the economy. Therefore, employability refers to a larger varietyof talents and attributes that will allow a person to succeed throughout their working life and gobeyond simply being able to find a job. Someone who recently earned their college oruniversity diploma is referred to as a new graduate. After graduating from a variety of schoolsand universities around the world, thousands of students majoring in hospitality hunt foremployment each year. Others are employed by the employer during the campus placementperiod, while some of them find employment on their own. Unfortunately, some of them getturned down.Employability skills are highly valued by employers because they are far more difficult to teachthan job-specific abilities. Some employable traits are innate, while others can be learnedthrough training, employment, or regular practice. Even though they may not be mentioned ina job description, employability skills are crucial and can increase your appeal to potentialemployers. The biggest advantage of possessing these qualities is that they might make youstand out from other job applicants who are vying for the same position.The BSHM graduates should possess the performance skills to collaborate with others,especially during times of high demand. They should be able to interact with others effectivelythrough speaking, writing, and body language. They must be able to adapt quickly whenunexpected events arise at work. Graduates of the BSHM program should be able todemonstrate and adapt leadership. They have to develop time management skills so that theymay concentrate on taking things one step at a time. Whenever making a choice, they mustcarefully consider their opinion.
Keywords: Hospitality Management